Numerical modelling of erosional landforms driven by offshore groundwater flow on siliciclastic continental margins: a conceptual approach - Shubhangi Gupta; Shubhangi Gupta; Aaron Micallef (Frontiers in Earth Science)
Offshore freshened groundwater (OFG) has long been hypothesised to be a key factor shaping continental margins worldwide. Field observations from siliciclastic margins suggest strong causal links between sub-seafloor OFG flow and seafloor depressions, canyons and landslide scars. These links have been hard to validate due to a paucity of appropriate field data and difficulty in simulating the subsurface flow and geomorphic processes in the laboratory. Here we present a numerical study that simulates the geomorphic action of sub-seafloor OFG seepage in an idealised 3D continental margin. Analysis of the coupling conditions highlights the multiplicative nature of the primary driving mechanisms (seepage-induced erosion and slope instability), suggesting a continuous transition between flow- and stress-controlled landforms. We find that OFG can create landforms in siliciclastic margins when buried flow pathways exist. Shelf-break depth determines landform type and timing. Shelf-breaks deeper than the sea-level lowstand lead to shallow circular depressions in the mid-shelf region, while those shallower than the lowstand yield V-shaped and theatre-headed valleys in the outer shelf to upper slope. Landforms emerge during falling sea-levels, starting as pockmark trains along the edges of the buried channels. Sensitivity studies show that: (1) channel width and depth affect only landform size, not type, and (2) OFG-related landforms are mainly erosion-driven and can evolve into slope failures in coarse-grained sediments with low cohesive strength. Our model aligns with field observations of pockmarks, canyons, and landslides in various continental margin settings.